2021
DOI: 10.35196/rfm.2021.4.617
|View full text |Cite
|
Sign up to set email alerts
|

Actividad Antifúngica De Pesticidas Biológicos, Botánicos Y Químicos Sobre El Agente Causal De La Marchitez Vascular Del Jitomate

Abstract: La marchitez vascular del jitomate (Solanum lycopersicum L.) es una de las enfermedades más importantes que afecta la producción alrededor del mundo. El control biológico ha emergido como una de las alternativas más promisorias al uso de fungicidas químicos. El objetivo de esta investigación fue diagnosticar el agente causal de la enfermedad y probar la efectividad in vitro de compuestos comerciales biológicos, botánicos y químicos contra el patógeno. Se realizó el aislamiento monospórico del hongo, se extrajo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In the case of the fungicide Captan ® , Ayvar-Serna et al [54] observed that, under in vitro conditions, it inhibited 100% of mycelial growth of F. solani, the causal agent of root rot in tomato, at a concentration of 0.044 g. Another study by Shah et al [55] reported that this pesticide inhibited 75.90% of mycelial growth of pathogens at a concentration of 1000 µg mL −1 in vitro. Both studies presented higher values than those reported in the present investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the fungicide Captan ® , Ayvar-Serna et al [54] observed that, under in vitro conditions, it inhibited 100% of mycelial growth of F. solani, the causal agent of root rot in tomato, at a concentration of 0.044 g. Another study by Shah et al [55] reported that this pesticide inhibited 75.90% of mycelial growth of pathogens at a concentration of 1000 µg mL −1 in vitro. Both studies presented higher values than those reported in the present investigation.…”
Section: Discussionmentioning
confidence: 99%